Health care functions of ozone sterilizer - Ying-Qiu Gu; Guo-Hao Ning (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2023)
People's Daily life and physical health are often plagued by viruses and bacteria. The novel coronavirus epidemic several years ago has seriously affected the global economy and social life. In addition to vaccination, ecologically safe and long-term and effective disinfection methods are very necessary. Ozone is an efficient and broad-spectrum bactericidal disinfectant, and the trace level of ozone in the atmosphere can make many viruses and bacteria lose their biochemical activity and infectivity. Nature produces trace amounts of ozone in the air through lightning to achieve the purpose of purifying the ecological environment. The product of ozone decomposition is oxygen, without secondary pollution. Ozone sterilizer has been widely used in epidemic prevention and control in intensive breeding farms and has achieved remarkable effects. If the concentration and action time can be accurately controlled, then ozone can effectively eliminate pathogens without harming normal cells in the human body. Therefore, the use of mini household ozone disinfectors for personal epidemic prevention and health care is a topic worth serious research. Shanghai Finerule Company has done a lot of tentative work in this respect and has achieved some good results.